Improved Synthesis of Novel 2,4-Diamino-5-furfurylpyrimidine in Presence of Molecular Sieves - Rajapandi, R.; Singh, Jagadish; Maity, T.K. (Asian Journal of Chemistry, 2010)
Furfural undergoes base catalyzed condensations with b-ethoxy-propionitrile to give 3-ethoxy- 2-(furan-2-ylmethyl)acrylonitrile (3), which in turn reacts with methanolic guanidine in the presence of mole-cular sieves 3A (MS 3A) to give 2,4-diamino-5-furfurylpyrimidine (4) in fairly good yields.